2019
DOI: 10.1371/journal.pone.0225383
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study of drought tolerance and biomass allocation in wheat

Abstract: Genome wide association studies (GWAS) are important in discerning the genetic architecture of complex traits such as biomass allocation for improving drought tolerance and carbon sequestration potential of wheat. The objectives of this study were to deduce the population structure and marker-trait association for biomass traits in wheat under drought-stressed and non-stressed conditions. A 100-wheat (Triticum aestivum L.) genotype panel was phenotyped for days to heading (DTH), days to maturity (DTM), shoot b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 75 publications
(82 reference statements)
3
41
0
Order By: Relevance
“…The SNP markers used had a reproducibility value of 1, polymorphic information content (PIC) values ranging from 0.020 to 0.50, and a mean call rate of 0.93 ranging from 0.84 to 1.00. A total of 15 565 SNP markers and 93 genotypes were used after data imputation where SNP loci and individuals with <20% missing data and rare SNP, with <5% minor allele frequency (MAF) were pruned from the data before analysis following Mathew et al, [ 44 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SNP markers used had a reproducibility value of 1, polymorphic information content (PIC) values ranging from 0.020 to 0.50, and a mean call rate of 0.93 ranging from 0.84 to 1.00. A total of 15 565 SNP markers and 93 genotypes were used after data imputation where SNP loci and individuals with <20% missing data and rare SNP, with <5% minor allele frequency (MAF) were pruned from the data before analysis following Mathew et al, [ 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…Before association mapping, best linear unbiased predictors (BLUPs) were derived for the phenotypic traits using the random mixed model in DeltaGen software [ 50 ]. BLUPs minimise the effects of the environmental and seasonal variations, which eliminates the need to conduct marker-trait association for each environment independently [ 44 ]. The BLUPs were used as input in the GWAS analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Firstly, we declared significant QTL and SNPs based on false discovery rate (FDR < 0.05) as a cut-off point. However, the FDR was too stringent in this study, so we finally used a lower cut-off threshold using an unadjusted p -value of <0.001 to declare significant QTL ( Mwadzingeni et al, 2017 ; Sukumaran et al, 2018 ; Mathew et al, 2019 ). Visualization of significant QTL and SNPs was done using Manhattan plots with the qq man R package ( Turner, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, studies detected QTL associated with seedling heat tolerance-related traits ( Li et al, 2012 ; Maulana et al, 2018 ) and drought tolerance-related agronomic traits in wheat ( Mwadzingeni et al, 2017 ; Gahlaut et al, 2019 ). Studies have found marker–trait associations for drought stress tolerance on different chromosomes, including 1A, 2A, 2B, 2D, 3D, 4A, 4D, 5A, and 7B, of wheat ( Mwadzingeni et al, 2017 ; Shi et al, 2017 ; Sukumaran et al, 2018 ; Gahlaut et al, 2019 ; Mathew et al, 2019 ). However, few studies on drought tolerance of wheat have been conducted at the seedling stage.…”
Section: Introductionmentioning
confidence: 99%
“…A GWAS of 91 phenotypically diverse genotypes across 21 countries displayed two significant drought induced major alleles that cause long root lengths under polyethylene glycol (PEG)-induced water stress. The GWAS approach also identified three drought-responsive pleiotropic single nucleotide polymorphism (SNP) markers associated with root dry biomass in a panel of 100 bread wheat genotypes selected on the basis of their breeding history for drought tolerance ( Mathew et al , 2019 ). Another study identified five significant markers causing extended rooting lengths under drought stress conditions using a mapping population consisting of two introgressed populations ( Bhatta et al , 2018 ).…”
Section: Genetics Of Root System Variation and Drought Stress Adaptatmentioning
confidence: 99%